Analisis Pengaruh Jumlah Penduduk, Pertumbuhan Ekonomi dan Inflasi Terhadap Kemiskinan di Provinsi Jambi - Abd Halim; Indria Mayesti; Rossa Anggraini (J-MAS (Jurnal Manajemen dan Sains), 2022)
Poverty is one of the biggest problems faced by all countries, especially developing countries like Indonesia. Therefore, it is necessary to analyze what factors influence poverty. The purpose of this study was to determine the development and influence of Population, Economic Growth and Inflation on Poverty in Jambi Province based on 2011-2020 data. This research is a quantitative research because the data that is processed is quantitative data such as data on population, economic growth, inflation and poverty. Sources of data obtained from the Central Statistics Agency (BPS) in the form of secondary data. The data analysis technique used is multiple regression analysis with IBM SPSS statistics and time series. The results show the results of the first hypothesis that the effect of population (X1) on poverty (Y) has a positive and insignificant effect with a probability value of 0.589, the effect of economic growth (X2) on poverty (Y) on a negative and insignificant effect with a probability value of 0.847, the effect of inflation (X3) on poverty (Y) there is a positive and insignificant effect with a probability value of 0.738. Simultaneously, it is found that population (X1), economic growth (X2) and inflation (X3) have a negative and insignificant effect on poverty (Y) in Jambi Province for the period 2011-2020.